Numerical simulation on the optical and electrical properties for heterojunction solar cell using Al2O3/ITO double layer anti reflective coating / Nurul Aina Nabihah Hamdan - Hamdan, Nurul Aina Nabihah (2022)
Solar cell has become one of the options to a greener world. Various studies has been done to achieve a solar cell with high efficiency and reasonable in price. To accomplish this study, heterojunction solar cells using Al2O3/ITO as the double layer anti-reflection coating are analyzed using the Wafer Ray Tracer simulation by the PV Lighthouse. The light trapping scheme use Al2O3 and ITO as the double anti-reflection coating (DLARC) to support the reflection, absorption and transmission (R, A, T) of the silicon solar cell. It acts as to minimises reflectance and improves the overall efficiency of the solar cell. The focus of DLARC variation is to increase absorption while decreasing reflection and transmission. High refractive index of the hydrogenated a-Si (a-Si:H) emitter layer generates excessive reflection losses in SHJ solar cells making the silicon wafer have a low absorption efficiency. The DLARC thickness and base angle are varied as part of the simulation using the Wafer Ray Tracer by PV Lighthouse. The surface morphology of upright pyramid texture, height is 3.536 μm, texture base angle 54.74°, width 5μm are used for reference scheme. Four schemes will be analyzed through out this study along with the reference scheme. The result of this study is, Scheme 3 gives the optimum result with 99% absorption, 21% reflection and 67% transmission. The objective of this study is to analyze the optimum thickness of ARC on optical and electrical properties are then achieved as the thickness and base angle of Scheme 3 varied gives the optimum result. Jmax value of Scheme 3 is also the highest with 0.3842 mA/cm2. In conclusion, the Wafer Ray Tracer from PV Lighthouse simulation can identify and analyzes the reflection, absorption and transmission of the silicon solar cell.